YEAR 10 - Goodger, Toby; Lacroix, Duncan; Khalique-brown, Hannah; Massy, Luke (Filmhub, 2026)
An apocalypse survivor must track down a group of cannibals in order to avenge his father. Written and directed by Benjamin Goodger, this dialogue-less post-apocalyptic thriller explores the fine line between human and animal.